A Note on the Proprietary and Entity Perspectives in Financial Statements: The Implications for two Current Controversial Issues. (2nd January 2018) - Schmidt, Martin
Abstract: Financial statements can portray the financial position and performance of an entity from different perspectives. Two dominant perspectives are the proprietary and entity perspectives. These perspectives also feature in recent discussions by the IASB and the FASB in relation to their conceptual framework project. The adopted perspective will yield different presentations for a number of issues. This paper illustrates the implications for two controversial issues currently under discussion by the IASB and the FASB: accounting for changes in a reporting entity's own credit risk when liabilities are measured at fair value, and the classification of certain obligations as either equity or liabilities. The paper explains why the adoption and consistent application of one perspective are important for standard setting and financial reporting to ensure the consistent presentation of an entity's performance and financial position that can be correctly interpreted by users of financial statements against the background of the chosen perspective.